MENTOR TEACHERS’ VOICES ON PRE-SERVICE ENGLISH TEACHERS’ PROFESSIONAL LEARNING - Kuswandono, Paulus (Indonesian Journal of Applied Linguistics, 2017)
Various studies have demonstrated that the role of mentor teachers in helping pre-service English teachers (PSETs) develop their professional experiences in school-based practicum is undeniably fundamental. Considering that mentor voices are still underrepresented in studies, this study aims to investigate the mentor teachers’ voices and beliefs to help the professional learning of pre-service English teachers (PSETs) in their school-based practicums. This is a qualitative study which involves seven mentor teachers who teach English in senior high schools in Indonesia. Data was gathered through questionnaires and unstructured interviews carried out in the participants’ school setting and analysed using NVIVO 9 (qualitative data analysis software). The findings reveal the mentor teachers’ beliefs in guiding PSETS during the school-based practicum. The mentor teachers viewed that PSETs need to learn and experience more fundamental aspects of teaching, namely interpersonal skills and emotional engagement in teaching, including their leadership. Implications for teacher education to improve the quality of relationship between PSETs and mentor teachers are addressed.